Sukuramu jissensha ga shirubeki 97 no koto - Verheyen, Gunther; Yoshiba, Ryūtarō; Harada, Kirō; Nagase, Miho (Orairī Japan, 2021)
"Improve your understanding of Scrum through the proven experience and collected wisdom of experts around the world. Based on real-life experiences, the 97 essays in this unique book provide a wealth of knowledge and expertise from established practitioners who have dealt with specific problems and challenges with Scrum. You'll find out more about the rules and roles of this framework, as well as tactics, strategies, specific patterns to use with Scrum, and stories from the trenches. You'll also gain insights on how to apply, tune, and tweak Scrum for your work. This guide is an ideal resource for people new to Scrum and those who want to assess and improve their understanding of this framework."--
Keywords: Agile software development; Scrum (Computer software development); Méthodes agiles (Développement de logiciels); Scrum (Développement de logiciels)